Perbandingan Akrilamidakopi Bubuk Tradisional Dan Luwak Dengan Metode HPLC - Ridho Asra; Rusdi Rusdi; Sofia Nofianti; Nessa Nessa (LLDIKTI Wilayah X, 2019)
Akrilamida merupakan senyawa kimia terdapat pada kopi yang disangrai pada suhu diatas 120 ˚C, berpotensi menyebabkan kanker pada manusia. Tujuan dari penelitian ini adalah untuk membandingkan kandungan akrilamida dalam kopi bubuk tradisional dan kopi luwak dengan metode Kromatografi Cair Kinerja Tinggi. Fase gerak yang digunakan asetonitril: aquabidest (15: 85, v/v), dengan detektor Photodioday-Array (PDA) pada ℷ 200 nm. Akrilamida dalam sampel kopi bubuk teridentifikasi pada waktu retensi (tR) ± 6,8 menit. Metode ini terbukti valid dengan linearitas y = 356468 + 293761 x, koefisien korelasi (r) = 0,9993, batas deteksi 1,9901 µg/mL dan batas kuantitasi 6,6337 µg/mL, presisi dengan % SBR = 0,207 %, akurasi dengan % perolehan kembali kopi bubuk tradisional dan kopi bubuk luwak 99 % dan 104 %. Kadar akrilamida dalam sampel kopi bubuk 1 sampai 6 berturut-turut adalah 1115 ± 12,17 µg/g sampel (1), 687 ± 7,58 µg/g sampel (2), 1461 ± 63,89 µg/g sampel (3), 221 ± 3,54 µg/g sampel (4), 128 ± 3,24 µg/g sampel (5), 195 ± 1 µg/g sampel (6). Dari keenam sampel kopi bubuk menunjukkan bahwa kadar akrilamida masing-masing sampel berkisar antara 128 sampai 1461 µg/g. Kadar yang diperoleh melebihi batas aman konsumsi akrilamida yang dikeluarkan oleh WHOAcrylamide is a chemical compound found in roasted coffee at temperatures above 120 ˚C which can potentially cause cancer in humans. The purpose of this research was to analyze acrylamide contents in traditional ground coffee and civet ground coffee by using High Performance Liquid Chromatography (HPLC) method. This analysis was carried out by isocratic elution system, the mobile phase of acetonitrile : aquabidest (15 : 85, v/v), using the stationary phase of the Shimadzu Shimpack ODS C18 column (250 × 4.6 mm), flow rate of 0.5 mL/minute, injection volume 20 µL, with a Photodioday-Array (PDA) detector at a wavelength of 200 nm. Acrylamide in ground coffee samples was identified at retention time (tR) ± 6.8 minutes. This method is proved valid with the linearity y = 356468 + 293761 x, correlation coefficient (r) = 0.9993, limit of detection 1.9901 µg / mL and limit of quantitation 6.6337 µg / mL, precision with % RSD = 0.207 %, acuracy with % recovery of traditional ground coffee and luwak ground coffee 99 % and 104 %. Acrylamide levels in 1 to 6 ground coffee samples in a row is 1115 ± 12.17 µg / g samples (1), 687 ± 7.58 µg / g samples (2), 1461 ± 63.89 µg / g samples (3), 221 ± 3.54 µg / g sample (4), 128 ± 3.24 µg / g sample (5), 195 ± 1 µg / g sample (6). Of the six ground coffee samples showed that the acrylamide levels of each sample ranged from 128 to 1461 µg / g. The levels obtained exceed the safe limits of acrylamide consumption released by WHO